Dietary fatty acids differentially impact phagocytosis, inflammatory gene expression, and mitochondrial respiration in microglial and neuronal cell models - Butler, Michael J.; Mackey-Alfonso, Sabrina E.; Massa, Nashali; Baskin, Kedryn K.; Barrientos, Ruth M. (Frontiers in Cellular Neuroscience, 2023)
The consumption of diets high in saturated fatty acids and/or refined carbohydrates are associated with neuroinflammation, cognitive dysfunction, and neurodegenerative disease. In contrast, diets high in polyunsaturated fatty acids are associated with anti-inflammatory and neuroprotective effects. We have previously shown that high fat diet (HFD) consumption increases saturated fatty acids and decreases polyunsaturated fatty acids in the hippocampus. We have further shown that HFD elicits exaggerated neuroinflammation and reduced synaptic elements, and results in robust memory deficits in aged rats. Here, we examined the impact of palmitate, an abundant dietary saturated fat, on a variety of cellular responses in BV2 microglia and HippoE-14 neurons, and the extent to which the omega-3 fatty acid, docosahexaenoic acid (DHA), would buffer against these responses. Our data demonstrate that DHA pretreatment prevents or partially attenuates palmitate-induced alterations in proinflammatory, endoplasmic reticulum stress, and mitochondrial damage-associated gene expression in both cell types. Furthermore, we show that synaptoneurosomes isolated from aged, HFD-fed mice are engulfed by BV2 microglia at a faster rate than synaptoneurosomes isolated from aged, chow-fed mice, suggesting HFD alters signaling at synapses to hasten their engulfment by microglia. Consistent with this notion, we found modest increases in complement proteins and a decrease in CD47 protein expression on synaptoneurosomes isolated from the hippocampus of aged, HFD-fed mice. Interestingly, palmitate reduced BV2 microglial phagocytosis, but only of synaptoneurosomes isolated from chow-fed mice, an effect that was prevented by DHA pretreatment. Lastly, we measured the impact of palmitate and DHA on mitochondrial function in both microglial and neuronal cell models using the Seahorse XFe96 Analyzer. These data indicate that DHA pretreatment does not mitigate palmitate-induced reductions in mitochondrial respiration in BV2 microglia and HippoE-14 neurons, suggesting DHA may be acting downstream of mitochondrial function to exert its protective effects. Together, this study provides evidence that DHA can ameliorate the negative impact of palmitate on a variety of cellular functions in microglia- and neuron-like cells.